Քարվաճառի էթնիկ դիմագծի հարցի շուրջ - Չոբանյան, Պավել («Զանգակ - 97»)
Until 19 centuary Armeniens had been che only inhabicancs of Karvachar. Thus, although there is evidence of kurds' first entrance in Karvachar in the 18th centuary, however, their mass in flow took place, in particular, in the first half of the 19й" Century and they lived on the abby's lands as tenants. Armenians began to lose their echnic majority since the mid of the 19й1 Century The church virtually, also lost i'ts land and landowner rights in second half of the 19th Century and, especially, at the end of the Century.
Keywords: Ազգագրություն; Պատմություն